STRATEGIES OF MAINTENANCE MODEL FOR EXERCISE BOOK MANUFACTURING MACHINE ON PAPER INDUSTRY BY IMPLEMENTING MONTE CARLO SIMULATION APPROACH - Astuti, Fina Andika Frida; Sugiono, Sugiono; Choiron, Moch Agus (JEMIS (Journal of Engineering & Management in Industrial System), 2017)
PT. XYZ is one of many paper manufacturing companies in East Java which produces Exercise Book. The company implements corrective engine maintenance system where new components replacement is done when the engine is damaged. This treatment system resulted in frequent engine sudden stopping. With so many breakdown frequencies resulting from the fact that the engine stops abruptly, the broken raw materials increases in number and causes losses for the company. To overcome that problem we need appropriate treatment strategies to minimize the frequency of breakdown. Another aim is to minimize downtime and maintenance costs incurred because of engine maintenance activity. There are 3 maintenance scenarios implemented to solve such problem, i.e. scenario based on the existing condition of the company, scenario of component replacement in accordance with Mean Time to Failure (MTTF) value, and scenario of component replacement when the reliability of the component has reached 70%. From those three scenarios we will manually carry out an interval maintenance planning and Monte Carlo simulation. The result of data processing shows that in order to minimize the number of Exercise Book engine breakdown we can apply the 3rd scenario namely the replacement of component when the reliability of component has reached 70%. To minimize the amount of downtime and maintenance costs appropriately we shall use scenario 2, namely the replacement of component based on the Mean Time To Failure (MTTF) value. Â